PENGALAMAN AKSEPTOR DALAM MENGGUNAKAN KONTRASEPSI IMPLAN:STUDI KUALITATIF FENOMENOLOGI (LITERATURE REVIEW) - Geby Zahara As-Syifa. Sy; Asmanidar Asmanidar; Yushida Yushida; Juliastuti Juliastuti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Background: Implant contraception is one of the Long-Acting Reversible Contraceptives (LARCs) with high effectiveness in preventing pregnancy. Despite its numerous advantages, the use of implants has not been optimal due to various factors, one of which is the subjective experiences of acceptors during use. An in-depth understanding of acceptors' experiences is crucial for improving family planning services and implant coverage in Indonesia. Objective: This study aims to identify and analyze the experiences of acceptors in using implant contraception through a review of various published qualitative phenomenological studies. Method: This study employed a literature review design with a qualitative phenomenological approach. Articles were searched through PubMed, Google Scholar, Garuda, and National Journal Portal databases using keywords such as